Cytotoxicity of new calcium aluminate cement (Endobinder) containing different radiopacifiers - Huck, Claudia [UNESP] (2017)
This study aimed to evaluate the cytotoxicity of a calcium aluminate cement (EndoBinder) containing different radiopacifiers, Bi2O3, ZnO or ZrO2, compared with Mineral Trioxide Aggregate (MTA). According to ISO 10993-12:2012 (E) recommendations, 0.2 g of each cement were applied in transwell inserts and placed in 24-well culture plates containing 1 mL of culture medium (DMEM). After 24 h of incubation, the extracts (DMEM containing components released from the cements) were applied to immortalized odontoblast-like MDPC-23 cells. Cell viability (MTT test), alkaline phosphatase activity (ALP), total protein production and cell morphology (Scanning Electron Microscopy - SEM) were evaluated. The volume of 50 μL of extract was used to determine the chemical elements released by the cements using Energy Dispersive Spectroscopy (EDS). The following groups were established (n=6): NC - negative control (without treatment); EB - EndoBinder without radiopacifier; EBBO - EndoBinder+Bi2O3; EBZnO - EndoBinder+ZnO; EBZrO - EndoBinder+ZrO2 and WMTA - White MTA. Data were subjected to statistical analysis (Kruskal-Wallis test, level of significance=5%). Cells exposed to the different versions of EndoBinder presented small reduction in viability, total protein production and ALP activity, with values similar to the NC and WMTA groups (p>0.05). Different elements (C, O, Na, Al, P, Si, Cl, Bi, K) released by the cements were detected in the extracts. However, the cells had no significant changes in their morphology. EndoBinder and MTA did not affect negatively the metabolism of the odontoblastic-like cells, showing it to be cytocompatible, irrespective of the used radiopacifier.